2018
DOI: 10.2172/1501823
|View full text |Cite
|
Sign up to set email alerts
|

Crystalline Silicotitanate ion exchange media long-term storage evaluation

Abstract: Some of the distribution coefficient (K d ) values in Table ES-1 indicate that the measured value exceeds the calculated value. This difference in measured versus predicted is attributed to error in the measurements and reference state of the material. Because of the way that the distribution coefficient is calculated, small variance in measurements of mass and analytical instrument results can cause large changes in the observed value. The predicted distribution coefficients were calculated using the ZAM comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 6 publications
(11 reference statements)
4
16
0
Order By: Relevance
“…Cesium loading kinetic data was needed to conduct column performance comparisons (i.e., model predictions) for the two CST batches. a average and %RSD of replicate data b pre-wetted CST c analysis indicated that this data point may be low due to incomplete CST particle wetting during initial simulant contact d data reported previously (King, et. al., 2018a) SRNL-STI-2019-00088 Revision 0 The cesium loading data was analyzed using the ZAM Isotherm and VERSE Column models.…”
Section: Executive Summarymentioning
confidence: 63%
See 3 more Smart Citations
“…Cesium loading kinetic data was needed to conduct column performance comparisons (i.e., model predictions) for the two CST batches. a average and %RSD of replicate data b pre-wetted CST c analysis indicated that this data point may be low due to incomplete CST particle wetting during initial simulant contact d data reported previously (King, et. al., 2018a) SRNL-STI-2019-00088 Revision 0 The cesium loading data was analyzed using the ZAM Isotherm and VERSE Column models.…”
Section: Executive Summarymentioning
confidence: 63%
“…A sample of IE-911 CST Lot #2081000056 (Mat. #80562-556p, Drum #36232-1-5) stored for many years at SRS was collected from a drum (described in detail in an earlier report, King, et al, 2018a) and sub-sampled for batch contact testing as described above for R9120-B CST. The IE-911 media had been provided by UOP in the caustic-washed, sodium form and was not further preconditioned or treated by SRNL prior to testing.…”
Section: Cst Media Pretreatment and Sample Collection Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The R9140-B batch is a recently prepared CST batch while the IE-911 CST media has been stored at SRS for nearly two decades. Recent batch contact testing with the IE-911 CST batch and SRS Average simulant confirmed that the cesium removal performance of this batch had not changed significantly during storage [10].…”
Section: Experimental Methods and Modeling Approach 21 Cst Media Prementioning
confidence: 78%